Anti-semitism in Poland and Ukraine the belief om Jewish control as a mechanism of scapegoating - Bilewicz, Michal; Krzeminski, Ireneus (2010)
Systemic transition in post-communist Eastern Europe resulted in high inflation, rapid economic changes, and increased lack of control in everyday life. At the same time, anti-Semitic incidents were reported in this region after 1989. The ideological model of scapegoating (Glick 2002; 2005) might serve as an explanation of anti-Semitic prejudice in post-transition Eastern Europe. The model predicts that the ideology defining Jews as powerful, cunning, and dangerous would gain popularity in times of crises and would lead to greater discrimination against Jews. In two nationwide representative sample studies of anti-Semitism, in Poland (n = 1098) and Ukraine (n = 1000), we applied the ideological model of scapegoating to study various forms of anti-Semitism(conspiracy-based belief in Jewish control and discriminatory intentions toward Jews). In both samples, economic deprivation led to increased discriminatory intentions toward Jews; however, only in the Polish sample was deprivation linked with higher beliefs in Jewish control (scapegoat-defining ideology). In Poland the rise of conspiracy beliefs about Jewish control partially explained the effect of deprivation on discriminatory intentions toward Jews. The implications of these results are discussed.